Genealogia Muminków w genologicznej ramie. Czy muminkowe książki to saga? - Dymel-Trzebiatowska, Hanna (Zagadnienia Rodzajów Literackich, 2023)
The nine-volume series about the Moomins (1945–1970) by the Swedish-speaking Finnish writer and painter Tove Jansson has received broad international recognition since the first book, The Moomins and the Great Flood, was published in 1945. The series is widely considered to be a timeless classic for children, with this reputation predominantly resting on the enduring values of love, tolerance, and non-materialism it champions. It also includes philosophical intertexts that are transparent to adults, which makes it a multiple-address read. While the books about Moominvalley have been translated into over fifty languages and eagerly explored from different viewpoints, the article proposes a new perspective and elucidates their generic affiliation. It reflects on the reasons why they are labelled with theumbrella term ‘Moomin books’ (Swedish: muminböckerna), which does not indicate their genre, and makes a case for calling the series a saga. Grounded on the distinctive features of the saga and including references to Jansson’s biography, the analysis shows that the series pictures a genealogy of the Moomins, weaves intricate family relations and covers a considerable timespan. Furthermore, if the original publication chronology is followed, it features linearity and temporal progress. The conclusion is that classifying the Moomin series as a saga is legitimate, particularly in terms of cognitive genology.